Solar-Driven Hydrogen Peroxide Production Using Polymer-Supported Carbon Dots as Heterogeneous Catalyst - Gogoi, Satyabrat; Karak, Niranjan (Nano-Micro Letters, 2017)
Safe, sustainable, and green production of hydrogen peroxide is an exciting proposition due to the role of hydrogen peroxide as a green oxidant and energy carrier for fuel cells. The current work reports the development of carbon dot-impregnated waterborne hyperbranched polyurethane as a heterogeneous photo-catalyst for solar-driven production of hydrogen peroxide. The results reveal that the carbon dots possess a suitable band-gap of 2.98 eV, which facilitates effective splitting of both water and ethanol under solar irradiation. Inclusion of the carbon dots within the eco-friendly polymeric material ensures their catalytic activity and also provides a facile route for easy catalyst separation, especially from a solubilizing medium. The overall process was performed in accordance with the principles of green chemistry using bio-based precursors and aqueous medium. This work highlights the potential of carbon dots as an effective photo-catalyst. Highlights: 1 Polyurethane-supported carbon dots were developed as heterogeneous catalyst, and the developed catalyst was biodegradable. 2 Solar-driven H2O2 production from water, ethanol, and oxygen was achieved.